Climate- and human-driven variations in lake area and number in North Xinjiang, China. Issue 2 (17th January 2021) - Zhang, Jie; Zhou, Jinlong; Zhang, Guoqing; Ji, Yuanyuan; Zeng, Yanyan; Fan, Wei; Aikelamu, Ailihamu
ABSTRACT: Changes in the surface area of lakes can indicate climate change and human activity, and there are few reports on the characteristics of such changes in North Xinjiang, China. The normalized difference water index (NDWI) was modified by using the middle infrared band (MIR) instead of the near infrared band (NIR). The modified NDWI (MNDWI) can effectively extract the lake boundary. Changes in the number and area of lakes (surface area > 1 km 2 ) were examined using topographic maps (1:100, 000) and Land Remote-Sensing Satellite (System, Landsat) series images (multispectral scanner, thematic mapper, enhanced thematic mapper plus, and operational land imager) for the period from 1960 to 2018. The results showed that more than 85.00% of the lakes were identified in the Erqis River Basin (ErRB), Ulungur River Basin (URB), and Central North Tianshan (CNT) between 1960 and 1980, few lakes were observed in the Ebinur Lake Basin (ELB), Jimunai River Basin (JRB), Emin River Basin (EmRB), Guerbantonggute Desert Area (GDA), and Ili River Basin (IRB), and no lakes were observed in the Eastern North Tianshan (ENT). The surface area and numbers of lakes in North Xinjiang were increased by 795.99 km 2 (35.54%) and 39 (195.00%), respectively, between 1960 and 2018. Multiple factors influenced the changes observed for different types of lakes. The number and surface area of mountain lakes fluctuated and increased mainly in response to precipitation and temperature. The number of oasis lakes remained unchanged until 1990, but then increased in response to precipitation and temperature. The fluctuations in the surface area of oasis lakes, which were affected by climate and groundwater development, were relatively small between 1960 and 1990, but then became larger. However, the number and surface area of plain lakes increased between 1960 and 2018 and were mainly influenced by climate change and human activity, such as water diversion for irrigation, ecological restoration projects, and the implementation of the river chief system.